The Empowerment of Rawa Pening Communities in Enhancing Cleanliness and Environmental Sustainability - Retnowati Retnowati; Purwanto Purwanto; Hari Suryanto (Journal of International Conference Proceedings (JICP), 2020)
Rawa Pening is one of the villages in Semarang Regency, Central Java. It is known as an area with a lot of problems, especially those that are related to environmental damage and cleanliness. Obstacles that are faced by the Rawa Pening community are the lack of motivation and awareness about the importance of environmental cleanliness, mainly in terms of disposing trash around the Lake of Rawa Pening and water hyacinth weeds problem in the lake. The aims of this study are 1) Building a village empowerment program in Rawa Pening village to improve environmental sustainability and cleanliness, 2) Explaining the strategies, tips, and mechanisms performed by the community in pursuing environmental sustainability and cleanliness. This study used a qualitative method with data collection techniques through in-depth interviews and FGDs as well as involved observations. The solution that can be carried out to overcome the problem of environmental damage is by conducting socialization of Rawa Pening village movement through local culture and community empowerment programs. The result of the community empowerment program is that Rawa Pening village can improve cleanliness and environmental sustainability through cultural awareness. The Rawa Pening village movement has improved environmental sustainability and cleanliness. With the awareness through culture and local wisdom, the Rawa Pening community is committed to make sustainable efforts from the clean and healthy Rawa Pening movement program.